2020
DOI: 10.1097/ceh.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

A Perfect Match? A Scoping Review of the Influence of Personality Matching on Adult Mentoring Relationships—Implications for Academic Medicine

Abstract: Introduction: Mentoring is a widely regarded faculty development strategy in academic medicine. However, the lack of understanding about mentoring relationship dynamics limits effective recruitment, implementation, and evaluation. Despite decades of publications describing adult mentoring initiatives, few studies examine personality influence in mentoring relationships. This scoping review examined the extent, range, and nature of the research on personality matching in mentoring relationships, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This was surprising given that the HPI assesses qualities that describe how individuals relate to others and identifies how an individual is able to interact with other people as a predominant factor in social life success. 16 However, again the individuals who re-reviewed their results did report markedly more benefit of the HPI on their interpersonal relationships, further suggesting that introspective individuals may have a greater sense of awareness that improves interactions. Furthermore, even although residents reported a neutral to moderately positive impact of the HPI on their relationships with mentors, 74.2% of participants reported that they are satisfied or very satisfied with the mentorship they were receiving.…”
Section: Discussionmentioning
confidence: 95%
“…This was surprising given that the HPI assesses qualities that describe how individuals relate to others and identifies how an individual is able to interact with other people as a predominant factor in social life success. 16 However, again the individuals who re-reviewed their results did report markedly more benefit of the HPI on their interpersonal relationships, further suggesting that introspective individuals may have a greater sense of awareness that improves interactions. Furthermore, even although residents reported a neutral to moderately positive impact of the HPI on their relationships with mentors, 74.2% of participants reported that they are satisfied or very satisfied with the mentorship they were receiving.…”
Section: Discussionmentioning
confidence: 95%
“…Mentor and protégé personality traits can be important factors in mentoring relationships (Campbell & Campbell, 2007; Green & Bauer, 1995; Turban & Lee, 2007; Turban et al, 2017) and some (Bozionelos & Bozionelos, 2010; Huggett et al, 2020; Turban et al, 2017) have called for further research to investigate the relationship between personality traits and initiation of mentoring. This call has been heeded by a few investigators who have examined the influence of specific personality traits of mentors and protégés (Arora & Rangnekar, 2015; Turban et al, 2017; Waters, 2004) on mentoring relationships and some continue to advocate for research in this area (Turban et al, 2017).…”
Section: Personality and Mentoring Initiationmentioning
confidence: 99%
“…This call has been heeded by a few investigators who have examined the influence of specific personality traits of mentors and protégés (Arora & Rangnekar, 2015; Turban et al, 2017; Waters, 2004) on mentoring relationships and some continue to advocate for research in this area (Turban et al, 2017). Some studies have explored the five-factor model (FFM; Denissen et al, 2011; Huggett et al, 2020) of personality and its impact on mentoring, but none has explored specific facets of mentoring nor explored the influence of personality on the initiation of mentoring in graduate education, and more specifically in doctoral programs.…”
Section: Personality and Mentoring Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheong, 2014;Heeneman & de Grave, 2019;Sng et al, 2017); career development or progression (Efstathiou et al, 2018;Garr & Dewe, 2013;Ong et al, 2018;Pethrick et al, 2017;Stamm & Buddeberg-Fischer, 2011) and the mentoring of students (Buddeberg-Fischer & Herta, 2006;Farkas, Allenbaugh, Bonifacino, Turner, & Corbelli, 2019;Frei et al, 2010;Kalén, Ponzer, Seeberger, Kiessling, & Silén, 2012; M. P. Mann, 1992;Ng, Lynch, Kelly, & Mba, 2020;Skjevik et al, 2020). It seems that much of the research has focused on academic medicine (Cross et al, 2019;Farkas, Bonifacino, Turner, Tilstra, & Corbelli, 2019;Geraci & Thigpen, 2017;Huggett, Borges, Blanco, Wulf, & Hurtubise, 2020;Kashiwagi, Varkey, & Cook, 2013;Sambunjak et al, 2006) with fewer studies related to individual specialties (Lee et al, 2019;Y. X. Ng et al, 2020;Sayan et al, 2019) or indeed covering multiple medical specialties (C. W. S. Cheong et al, 2020;.…”
Section: Research Into Mentoringmentioning
confidence: 99%